2020
DOI: 10.1002/advs.202001572
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Chromosomal Structural and Dynamical Origin of Cell Differentiation and Reprogramming

Abstract: As an essential and fundamental process of life, cell development involves large-scale reorganization of the 3D genome architecture, which forms the basis of gene regulation. Here, a landscape-switching model is developed to explore the microscopic chromosomal structural origin of embryonic stem cell (ESC) differentiation and somatic cell reprogramming. It is shown that chromosome structure exhibits significant compartment-switching in the unit of topologically associating domain. It is found that the chromoso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 98 publications
(164 reference statements)
1
23
0
Order By: Relevance
“…expression, epigenetics and 3D genome architecture [3][4][5], the non-monotonic transitions in chromosome structure should also be expected during the reprogramming. With a landscapeswitching model, we observed the over-expanding chromosome structures, which are more open than those at the fibroblast and ES cells, during the reprogramming, resonating with the experimental evidence [45]. Here, we found that the chromosome during cell cancerization opens its structure and partially forms the structure, similar to the one formed in the ES cell.…”
Section: Plos Computational Biologysupporting
confidence: 80%
See 4 more Smart Citations
“…expression, epigenetics and 3D genome architecture [3][4][5], the non-monotonic transitions in chromosome structure should also be expected during the reprogramming. With a landscapeswitching model, we observed the over-expanding chromosome structures, which are more open than those at the fibroblast and ES cells, during the reprogramming, resonating with the experimental evidence [45]. Here, we found that the chromosome during cell cancerization opens its structure and partially forms the structure, similar to the one formed in the ES cell.…”
Section: Plos Computational Biologysupporting
confidence: 80%
“…The pathways are projected onto (A) the extensions of the longest and the shortest principal axes (PA1 and PA3), (B) the radius of gyration ( R g ) and the aspheric quantity (Δ), contact similarity in terms of the fraction of native contact Q to the IMR90 and A549 at (C) local range (0–2Mb), and (D) long-range (10–15Mb). The data of the ES cell are obtained from our previous work [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations